Growth and survival of cork oak (Quercus suber) seedlings after simulated partial cotyledon consumption under different soil nutrient contents (Plant and Soil, 2013)
We examined the importance of partial seed consumption (cotyledon loss) by rabbits in the early establishment of seedlings of cork oaks restricted to nutrient-impoverished soils. To determine the importance of cotyledons in the growth and development of seedlings, we simulated two levels of predation [light (30 % cotyledon loss) and heavy (60 % loss) partial consumption] and two soil nutrient contents (nutrient-poor soil, nutrient-rich soil). Seedlings height, root length, dry root and shoot biomass, specific leaf mass, leaf density, gas exchange, chlorophyll fluorescence parameters and photosynthetic pigment concentrations were determined. Results indicated that effect of nutrient level on the growth of the oak seedlings was more important than that of cotyledon biomass. However, in nutrient-poor soils, cotyledon biomass played a major role in the early performance of cork oaks. Acorns grown in nutrient-rich substrate, despite having greater aerial vigor, were slower to develop a vertical root, and hence less likely to reach permanent moisture. Cotyledon loss caused a decrease in the biomass of roots and shoots when acorns were heavily consumed, and as a result experienced a reduction in net photosynthetic rate, stomatal conductance and chlorophyll concentration. Survival of seedlings was unaffected by either soil type or cotyledon loss. Our results show that effects of soil type on the survival of oak seedlings were more important than those of cotyledon biomass. However, in a competitive situation, cotyledon biomass, as an indicative of growth nutrient support rather than an energy source, could be vital in a nutrient-poor environment, particularly in Mediterranean climate regions and for species with little inherent drought tolerance (as is the case of Quercus spp.), where rapid root growth is required to ensure that contact with soil moisture is maintained over the first summer.